Cross-Sectoral Collaboration in Stunting Prevention: Implementation in Donggala Regency, Central Sulawesi - Fajrillah Kolomboy; Adhyanti Adhyanti; Nurmiaty; Gusman Arsyad; Aminuddin Aminuddin; T. Iskandar Faisal; Kadar Ramadhan; Chen Hana W. Jun (Journal of Public Health and Pharmacy, 2025)
Introduction: The prevalence of stunting in Donggala Regency has increased from 29.5% in 2021 to 32.4% in 2022. The coordination system is not yet optimal, interventions are carried out separately and do not reach the target, and there is no monitoring and evaluation in stunting handling. The objective of the research is to analyze the implementation of cross-sectoral collaboration in stunting handling in Donggala Regency.